Direct transformation of raw biomass into a Fe–Nx–C single-atom catalyst for efficient oxygen reduction reaction. (3rd March 2021) - Wu, Danyang; Liu, Wei; Hu, Jinwen; Zhu, Chao; Jing, Hongyu; Zhang, Jiangwei; Hao, Ce; Shi, Yantao
Abstract : A C-SACs with the atomic dispersion of Fe–N4 sites has been prepared by the direct transformation of pig liver via the molten-salt-assisted pyrolysis. Abstract : Carbon-supported single-atom catalysts (C-SACs) are promising candidates for numerous electrocatalysis reactions. However, the controllable and economical synthesis of C-SACs remains a challenge since most of the examples were synthesized via multi-procedures and required elaborate selection of precursors, as well as severe sintering of the metal atoms as well. Herein, through high temperature carbonization in molten salts, we for the first time demonstrate a facile and low-cost strategy for the direct transformation of raw biomass into porous C-SACs with well-defined Fe–N4 sites (termed as Fe–N/C-SAC). The high polarity of molten salts mentioned above can provide a unique environment in which the aggregation of metal atoms is strictly restricted, and instead they are trapped by N atoms from the precursor of pig liver, a cheap raw biomass containing abundant proteins. As an ORR catalyst in an alkaline medium, Fe–N/C-SAC not only exhibits a considerable onset potential ( E onset = 0.89 V vs. RHE) but also gives a high limiting current density (5.64 mA cm −2 at 0.6 V), which is comparable to that of commercial Pt/C (5.80 mA cm −2 ). In addition, this C-SACs also illustrate excellent stability and methanol tolerance.